Os mecanismos de governança do saneamento básico no Brasil: um estudo de direito administrativo sob a perspectiva da economia dos custos de transação - Gonçalves, Leonardo Gomes Ribeiro (2015)
The water and sewage public service relevance is widely recognized. Nevertheless, there is high deficit level of access in Brazil, with different situations in the various country regions. In this sense, the objective of this dissertation is (i) from the interdisciplinary perspective of the Transaction Costs Economics, introduce an understanding of water and sewage public service in Brazil, currently regulated by Law No. 11,445/2007, (ii) evaluate the efficiency of the mainly used mode of governance, and (iii) eventually purpose alternative designs for the organization of the provision, economically superior in terms of reducing transaction costs for necessary investments to fulfill the fundamental objectives defined in art. 2 of Law No. 11,445/2007. The research used as a methodological strategy an interdisciplinary approach to law, economics and organizations, based on the new institutional economics. From the study of the basic institutional environment, with support in the theoretical framework, it was observed that the governance mechanism predominantly used to provide the water and sewage public service in Brazil, ie delegations to State Sanitation Companies through long-term contracts (program contracts) does not favor investments in specific assets (infrastructure) necessary for the supply and does not ensure policy goals. It was also found that there are viable alternatives to overall governance design, although the use of alternative forms probably are not feasible by implementing simple transplant standards, that is, by formal means. The modification of the prevailing water and sewage public service mode of governance, overcoming the verified low performance (low-level equilibrium), can not be held without charge. Therefore, it is necessary to overcome the costs for breaking the path dependence caused by hold-up carried out by the Sanitation State Companies to public service holders (municipalities), as well as costs for the disruption of path dependence in the Brazilian administrative law, which restricts the development of a legal theory of regulation to enable the construction of an adequate regulatory governance to reduce transaction costs in order to make viable investments in infrastructure assets with a high degree of specificity.